Interrelationships among genetic C677T polymorphism of 5, 10‐methylenetetrahydrofolate reductase, biochemical folate status, and lymphocytic p53 oxidative damage in association with tumor malignancy and survivals of patients with hepatocellular carcinoma. Issue 2 (29th August 2013) - Kuo, Chang‐Sheng; Huang, Chi‐Yun; Kuo, Hsing‐Tao; Cheng, Chin‐Pao; Chen, Chien‐Hung; Lu, Chin‐Li; Yang, Feili‐Lo; Syu Huang, Rwei‐Fen
<x xml:space="preserve">Abstract</x> Scope Metabolic genotypes of 5, 10‐methylenetetrahydrofolate reductase (MTHFR) and folate status on oxidative DNA lesions in hepatocellular carcinoma (HCC) has not been elucidated. The aims of the study were to investigate the folate‐polymorphic interactions on genetic oxidative damage in association with advanced HCC malignancy and prognosis. Methods and results The study included 232 HCC patients with folate nutrition, MTHFRC677T polymorphic, p53 genetic and tumour pathological data collected and analyzed for their survivals after a 7.8‐years following up. By adjustment for oxidative risk factors of HCC, the compound CT and TT genotypes in relative to the CC wild‐type were associated with 83% reduced lymphocytic p53 oxidative lesions of HCC patients with RBC folate lower than 688 ng/mL (OR: 0.17, 95%CI: 0.07–0.43). Such genetic protective effects by the CT/TT genotypes were 2‐fold enhanced among those with high RBC folate (OR: 0.08, 95% CI: 0.03–0.21, P for interaction < 0.001). For those with non‐folate‐deficient status, the compound CT and TT vs. CC genotypes were associated with 80% reduced risks of advanced HCC stages (III&IV) (OR: 0.2, 95%CI: 0.08–0.56). Such protection was negated either by adjustment of lymphocytic p53 oxidative lesions or by 3‐fold increased risks among those with high RBC status (OR: 0.6, 95%CI; 0.31–1.41, P for interaction = 0.009). Multivariate Cox proportional hazards analysis showed that the CT/TT genotypes vs. CC wild‐type were the independent predictable factor for better survival outcome of HCC patients (HR: 0.48, CI = 0.30–0.79). For CC homozygote, the second vs. the bottom tertile levels of RBC status were associated with 2‐fold increased mortality rate of HCC patients (HR: 2.05, CI = 1.0–4.1). Conclusion Our data demonstrated that reduced MTHFR activities associated with the MTHFRT allele may interact with RBC folate as the risk modifiers of lymphocytic p53 oxidative lesions of HCC patients. The CT/TT genotypes correlated with lower risks of late‐stage HCC and a favorable survival of HCC patients, depending on p53 oxidative lesions or RBC folate status.